Simulation Study of Nonlinear PI-Controller with Quasi-Z-Source Derived Push-Pull Converter - Chub, Andrii; Husev, Oleksandr; Vinnikov, Dmitri (Electrical, Control and Communication Engineering, 2013)
This paper is focused on the control issues of the quasi-Z-source derived push-pull converter with integrated magnetic elements. The proposed converter is intended for applications that require a high gain of the input voltage and galvanic isolation, i.e. power conditioning systems for renewable energy sources, such as variable speed wind turbines with direct driven permanent magnet synchronous generators. Magnitude and frequency of the output voltage of such turbines are variable due to intermittent nature of the wind power. Despite number of advantages converter has complicated dynamic behavior. Simulations showed change of stability margin depending on current operation point of the wind turbine and output load. Closed loop control system should provide fast response and stable operation in the wide range of wind speeds. Simulations showed that the conventional PI-controller with saturation cannot satisfy those requirements. Nonlinear PI-controller was derived by adding adjustment block to the conventional PI-controller. Adjustment block is drastically changing proportional and integral gains of the controller according to sign of the output voltage error. Proposed controller is compared with conventional one by means of simulation in PSIM. Simulation results prove that proposed nonlinear control system has improved regulator performance.